Pendampingan Taḥfiẓ Al-Qur’an di Desa Pakong Modung Bangkalan - Umar Zakka; Shonhaji Shonhaji; M. Tohir (Pusat Riset dan Inovasi Nasional, 2022)
Al-Quran tahfiz assistance at the Darus Sholah Pusat Islamic Boarding School (An-Nawawiyah) Pakong. The formulation of the problem raised in this community service activity is related to the effectiveness of tahfiz Al-Quran mentoring at the Pakong Darus Sholah Islamic Boarding School (An-Nawawiyah). The objectives of this PKM are: 1. to conduct training in effective time management 2. to hold deliberations to equally consider the benefits and benefits related to the constraints that exist in the tahfidz program at Islamic boarding schools 3. to facilitate the tahfidz program at the Islamic boarding school. The problem solving framework designed in the PKM activities in the form of implementing this training activity is: 1. Building effective time management to build conduciveness in carrying out the tahfid program at the Islamic boarding school. 2. Building the spirit of tahfidz members to build and help the tahfidz program run well. 3. Can develop a tahfid program that has a very efficient method. 4. Evaluation of training results. Based on interviews, questions and answers and direct observations during the activity, this community service activity yielded the following results: first, improving or developing methods in the tahfid program at the Islamic boarding school. Second, the creation of time management that is so efficient to support the existence of a method in the tahfid program at the boarding school. Third, the creation of souls who memorize the Koran who are calm in memorizing the Koran and can overcome all existing problems.